Health Education for children/ adolescents/ family: construction and validation of a scale - Fonseca Pereira, Anabela; Manuel Torres Almeida, Carlos; Manuel Torres Almeida, Carlos; Manuel Costa Pereira Rodrigues, Vitor; José Jacinto Escola, Joaquim (O Mundo da Saúde, 2020)
Health Education allows the development of behaviors capable of influencing the factors of a healthy life, namely the maintenance and improvement of the health status of the child/ adolescent/ family. Therefore, the perception of the importance of this practice by those who experience it (nurses and parents/family) can contribute strongly to its efficacy. Thus, this study aimed to build and validate an instrument for evaluating Health Education, carried out by nurses focused on children, adolescents, and/or family units. This was a descriptive, cross-sectional study developed in two phases: elaboration of items and their associations with the scale’s dimensions based upon a bibliographical review, exploratory interviews with nurses and parents/family members, analysis by experts (nurses), and subsequent validation using an exploratory factor analysis. The psychometric qualities of the scale were assessed by a sample of 603 individuals (nurses and parents/family), and studies of reliability, validity and internal consistency were also carried out. The results of the exploratory factor analysis identified three factors: “partnership of care with the child/ adolescent/ family”; “Health literacy”; “Promotion of healthy environments and health behaviors” with 48 items. Analyses included high item-factor correlation (≥0.70); Cronbach’s alpha=0.987; Kaiser-Meyer-Olkin=0.987; statistical significance within Bartlett’s sphericity test (p<0.001). The total explained variance was 65.7%. We can conclude that the Health Education assessment tool for the child/ adolescent/ family contexts, in addition to meeting the validity requirements, presents positive results for its use in the Health Education assessments carried out for the child/ adolescent/ family members.